On the enhancement of the fatigue fracture performance of polymer matrix composites by reinforcement with carbon nanotubes: a systematic review - Muhammad Ismail, A. H.; Al-Oqla, Faris M.; Risby, M. S.; Sapuan, S. M. (Springer, 2022)
Rapid development of carbon nanotubes (CNTs) reinforced to polymer composites has been recently noticed in many aspects. In this work, the latest developments on fatigue and fracture enhancement of polymer composites with CNTs reinforcement with diverse methods are thoroughly compiled and systematically reviewed. The existing available researches clearly demonstrate that fatigue fracture resistance of polymer composites can be improved accordingly with the addition of CNTs. However, this work identifies an interesting research gap for the first time in this field. Based on the systematic reviewing approach, it is noticed that all previously performed experiments in this field were mostly focused upon studying one factor only at a time. In addition, it is also addressed that there were no previous studies reported a relationship or effect of one factor upon others during examining the fatigue fracture of carbon nanotubes. Moreover, there was no adequate discussion demonstrating the interaction of parameters or the influence of one parameter upon another when both were examined simultaneously. It is also realized that the scope of the conducted fatigue fracture studies of carbon nanotubes were mainly focused on microscale fatigue analysis but not the macroscale one, which can consider the effect of environment and service condition. In addition, the inadequacy of fatigue life predicting models via analytical and numerical methods for CNT-reinforced polymer composites have also been highlighted. Besides, barriers and challenges for future directions on the application of CNT-reinforced polymer composite materials are also discussed here in details.